2018
DOI: 10.1111/sdi.12663
|View full text |Cite
|
Sign up to set email alerts
|

Role of telehealth in renal replacement therapy education

Abstract: The prevalence of end-stage renal disease is rising in the United States, which bears high financial and public health burden. The most common modality of renal replacement therapy (RRT) in the United States is in-center hemodialysis. Many patients report lack of comprehensive and timely education about their treatment options, which may preclude them from participating in home-based dialysis therapies and kidney transplantation evaluation. While RRT education has traditionally been provided in-person, the ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 39 publications
0
9
0
1
Order By: Relevance
“…Studies have shown that using remote technology-based education such as websites, smartphone applications, and social networks as a strategy has increased knowledge, medication adherence, and patient education effectiveness in transplanted recipients. [ 37 38 39 ] From the participants' point of view, teamwork patient education was one of the key elements of patient education. This is consistent with the study of Farahani et al ., in which lack of collaboration and coordination between health-care providers in health education was identified as a problem by the participants.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that using remote technology-based education such as websites, smartphone applications, and social networks as a strategy has increased knowledge, medication adherence, and patient education effectiveness in transplanted recipients. [ 37 38 39 ] From the participants' point of view, teamwork patient education was one of the key elements of patient education. This is consistent with the study of Farahani et al ., in which lack of collaboration and coordination between health-care providers in health education was identified as a problem by the participants.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with in-person KRT education, content delivered using telehealth has the benefits of being flexible, adaptable to patient learning styles/preferences, and easily amenable to repetition and reinforcement. 10 Potential resources are outlined below: Reinforcing education around uremia may reduce the risk of clinical deterioration at home and subsequent "crash starts," hospitalizations and other adverse outcomes, which have been experienced in some European centers (personal communication Markus van der Giet). Educational material on sick-day rules (suggested medication changes on days when the patient is unwell enough to do their usual activities) may help to avoid preventable acute kidney injury (AKI) and other adverse outcomes that may result in avoidable contact with the healthcare system.…”
Section: Patient Education and Supportmentioning
confidence: 99%
“…Compared with in-person KRT education, content delivered using telehealth has the benefits of being flexible, adaptable to patient learning styles/preferences, and easily amenable to repetition and reinforcement. 10 Potential resources are outlined below:…”
Section: Suggestionsmentioning
confidence: 99%
“…Entre las más relevantes destacan aquellas dirigidas al control clínico a distancia de pacientes con enfermedad renal crónica [3][4][5] , interconsulta al nefrólogo desde el primer nivel de atención 6,7 , control periódico de pacientes incluidos en programas de diálisis peritoneal [8][9][10][11][12] , manejo protocolizado de complicaciones de la diálisis peritoneal 13 , control de hemodiálisis (HD) domiciliaria y reclutamiento de pacientes para las listas de trasplante renal 5 , entre otras. Además de estas estrategias asistenciales directas, se han desarrollado programas dirigidos a potenciar la asistencia nefrológica interdisciplinaria 14,15 , educar a grupos de pacientes en el conocimiento y manejo de opciones de terapia de reemplazo renal (TRR) y optimizar las estrategias de autocuidado de pacientes en TRR 16,17 . Algunas de estas estrategias se ven auxiliadas por dispositivos de telemedicina que permiten monitorizar a distancia y en forma automática parámetros objetivos, como peso, presión arterial, temperatura, saturación de oxígeno e, incluso, la diálisis domiciliaria y el diagnóstico mediante telepatología 5 .…”
unclassified